Application of Quality Function Deployment (QFD) to a Lever Operated Knapsack (LOK) Sprayer - Awang, Mohamad (2000)
A need to improve the present lever operated knapsack (LOK) sprayer specifications by referring to its users' specific wants and needs or voices of customers (VOC) was proposed. Quality function deployment (QFD) was adopted to systematically determine the priority items through the construction of the Phase I matrix house of quality (HOQ). Based on customer importance rating (IR) and complaints, the priority VOC related to ergonomics, performance, safety, and economy aspects of the LOK sprayer were determined. The VOC were comfortable tank, stable, less pumping, comfortable strap, light in weight, durable strap, durable trigger, durable washer/rubber seals, durable tank, selection of nozzle, and no leaking. Through the analysis of HOQ, the priority technical requirements of the LOK sprayers were finally derived based on their high relationship with the priority VOC. The prioritized technical requirements were overall weight, leakage limit, level of body contour, height, width, depth, setting' price, tank material, lance length, strap width, length, softness level, easy to adjust, pumping frequency, setting pressure, trigger material and nozzle compatibility. The nature and degree of change to some technical requirements as caused by changes in some others could be systematically identified through a co-relationship matrix. Through these priority technical requirements which highly correspond to the VOC of the LOK sprayers, the manufacturer will have a guideline to focus on specification improvement of the LOK sprayers in the search to systematically meet the users' requirements. Finally, these improvements are able to increase the users' satisfaction towards manufactured LOK sprayers as the prioritized technical requirements are associated with items of their concern.